Avaliação da dinâmica espacial e temporal da vulnerabilidade ambiental da zona costeira sul do estado da Paraíba - Malzac, Marie Eugénie (2019)
The evolution of the occupation of the Brazilian coastal geographical space has been an important issue to be faced by environmental planners, as there is a need for compatibility between anthropic activities and the carrying capacity of the land, seeking to minimize environmental vulnerability in the their various ecosystems. Knowledge of environmental vulnerability should be extended over time by analyzing spatial growth trends with a view to establishing appropriate environmental zoning policies. The southern coastal zone of Paraíba State (ZC-Sul / PB), object of this study, has suffered over the centuries with the destruction of the Atlantic Forest, replaced by the majority occupation of agricultural activity, especially sugar cane, besides of urban sprawl. The research, reported in this thesis, aimed to elaborate cartograms of the degrees of environmental vulnerability to soil loss destined to the evaluation of the relative stability of the morphodynamic categories, associated with the morphogenesis / pedogenesis relationship, in ZC-Sul / PB for past and predictive scenarios. Issues related to the Coastal Zone (ZC) are addressed with emphasis on the delimitation of its geographical space in the international and Brazilian context. Integrated management within the river basin and ZC has guidelines set out from the environment, sea and water resources policies. Therefore, a conceptual diagram concerning the water resources planning zones and the coastal zone was presented, as well as the delimitation of the ZC-Sul/PB, in the light of criteria established in the literature, and the arbitrary criterion, regarding to the BR-101 highway layout, was considered to be the most appropriate. The mapping of the dynamics of land use and occupation classes (UOS) changes in the ZC-Sul/PB was performed, in the past scenarios for 1988, 2001 and 2013, using satellite images for processing through of supervised automatic interpretation and classification techniques software. UOS predictions were also made for the years 2023 and 2033 with the Land Change Modeler (LCM) model, making it possible to predict the changes. Due to the lack of UOS database, the application of the LCM model to the ZC-Sul/PB was based on the transition parameters for the municipality of Pitimbu, in which the validation was performed, and also considering the similarities observed between the evolution of the UOS in Pitimbu and ZC-Sul/PB. Temporal and spatial analyzes of past and predictive scenarios have identified results of major changes in areas of the Atlantic Forest subsystems, for the Miscellaneous Crops, Sugarcane and Urban Areas classes. For the environmental vulnerability assessments in the ZC-Sul/PB in future scenarios, as dependent only on changes in land use and occupation, it was necessary to ensure that there are no trends in the region's rainfall time series. Thus, two nonparametric methods were applied to verify the occurrence of trends of the precipitation series, and the results were indicative of the absence of trends. The evolution analysis of environmental vulnerability to soil loss showed the occurrence of four grades of environmental vulnerability classification in ZC-Sul/PB: Moderately stable, Medium stable/vulnerable, Moderately vulnerable and Vulnerable. From the examination of the environmental vulnerability cartograms, it was possible to infer a clear repercussion of the changes of the UOS, with the decrease of forested areas, and the increase of the vulnerability levels in the ZC-Sul/PB, since the other thematic plans were considered invariable in the referred time scale. The comparison of past and predictive scenarios led to the conclusion that the intermediate morphodynamic category prevailed in pedogenetic/morphogenetic equilibrium in the scenarios for 2001 and 2013, with a Median Stable / Vulnerable degree, equivalent to 56.83% and 52.99% respectively. The scenario for the year 2033 points to a change to the unstable category situation, prevailing morphogenesis, totaling 53.22%, with Moderately Vulnerable and Vulnerable degrees, thus indicating a propensity for soil loss. The intermediate morphodynamic category, observed between 2001 and 2013, with the recognition of the pedogenetic / morphogenetic balance for most of the ZC-Sul / PB, goes on to predict the condition of morphogenesis, unstable category, from 2025.